Kendala Sekolah dalam Pengadaan Laboratorium IPS di MTs Negeri Kabupaten Demak - Suryaningsih, Putri; Miftah, Agus; Fatmawati, Noor (ILUMINASI: Journal of Research in Education, 2024)
This study aims to determine the obstacles in the procurement of social studies laboratories in Mts Negeri Demak Regency. This research was conducted at Mts Negeri 4 Demak and Mts Negeri 6 Demak. The type of research used is qualitative descriptive, which describes the procurement of social studies laboratories at the State Mts level. The subjects studied were the Principal and social studies subject teachers at Mts Negeri Demak Regency. The data collection techniques used were observation, interviews and documentation. Researchers found that obstacles in the procurement of social studies laboratories in general are contained in several obstacles, namely madrasahs that are still new, priority scale constraints, funding constraints, to space constraints.